Land conflicts in Formosa, Argentina (1884-1958) - Girbal, Noemi Maria (2014)
Formosa is located in Northeast Argentina and gained state status in 1884 with a weak political identity. There are few studies in Argentine historiography that have studied social actions and public policies in the region. Precarious settlement plans and poor communication led to conflicts over lands. The indigenous population was disciplined by the state and the Catholic Church. Meanwhile, many factors promoted a population exodus: untrained farmers, poorly demarcated plots, crop production attacked by pests and soil erosion. This historical study focuses on the settlement and construction of space in Formosa, which was historically the poorest region of Argentina. Social conflicts are revealed in the analysis of national government policies and their implementation within territorial logics, especially those related to the use of common property resources.